Rent control effects through the lens of empirical research - Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Rent control is a highly debated social policy that has been omnipresent since World War I. Since 2010s, it has been experiencing a true renaissance, for many cities and countries facing housing shortage are desperately looking for solutions of the chronic housing shortage and direct their attention to controlling housing rents and to other restrictive policies. Is rent control useful or does it create more damage than utility? In order to answer this question, we need to know what are the effects of rent control. This study overviews a large empirical literature looking at various aspects of rent controls. We come to conclusion that rent controls are quite effective in terms of lowering housing rents or slowing down their growth, but they also lead to a wide range of adverse effects impacting both landlords and tenants.
Keywords: 330